A new genus and first Cenozoic fossil record of moth lacewings (Neuroptera: Ithonidae) from the Early Eocene of North America - Makarkin, Vladimir N.; Archibald, S. Bruce (Zootaxa, 2009)
A new genus and species Allorapisma chuorum gen. sp. nov. is described from the Early Eocene locality at Republic, Washington, U.S.A. The forewing venation of Allorapisma is most similar to that of the genus Principiala Makarkin & Menon from the Early Cretaceous of Brazil and Britain. A new, informal suprageneric taxon consisting of these genera is proposed, the Principiala group. The habitats of extant and fossil Ithonidae are briefly discussed.